If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80 = 3x Solving 80 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 80 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 80 + -3x = 0 Add '-80' to each side of the equation. 80 + -80 + -3x = 0 + -80 Combine like terms: 80 + -80 = 0 0 + -3x = 0 + -80 -3x = 0 + -80 Combine like terms: 0 + -80 = -80 -3x = -80 Divide each side by '-3'. x = 26.66666667 Simplifying x = 26.66666667
| -181+2x=12x+79 | | 15u-12u=18 | | 110/28 | | 5(4x-2)+6=-1 | | 2(x-6)+5=3(2x-4) | | 6xy/16y | | 5+4g=7 | | 3/4+3=1/2 | | 3v+5v=8 | | K-10=-4 | | 2(.5)+10=11 | | (63)2+2(4x+3)=16x-12 | | 18h-8h=20 | | 4b+2=-10-8b | | 32-4.5/4= | | 3/4t+3=1/2 | | 20h-18h-(-4h)+-h+3h=16 | | 15b-14b=5 | | 1/7.8 | | 0=x^2+3x-162 | | z^3=125 | | 17=K+-12 | | 4-5(x-3)+2x=-3 | | 45x+y=10 | | 4(7-1)=2z-4 | | 360=b-10 | | 1600/x^2 | | 5n-4=4+3n | | -7x+20=-3x-8 | | 2(x-5)+3=3(x+2)+8 | | T/42=1.5/3 | | -15u+13u=14 |